Multi-scale molecular photoacoustic tomography of gene expression. - Xin Cai (Public Library of Science (PLoS), 2012)
Photoacoustic tomography (PAT) is a molecular imaging technology. Unlike conventional reporter gene imaging, which is usually based on fluorescence, photoacoustic reporter gene imaging relies only on optical absorption. This work demonstrates several key merits of PAT using lacZ, one of the most widely used reporter genes in biology. We show that the expression of lacZ can be imaged by PAT as deep as 5.0 cm in biological tissue, with resolutions of ∼1.0 mm and ∼0.4 mm in the lateral and axial directions, respectively. We further demonstrate non-invasive, simultaneous imaging of a lacZ-expressing tumor and its surrounding microvasculature in vivo by dual-wavelength acoustic-resolution photoacoustic microscopy (AR-PAM), with a lateral resolution of 45 µm and an axial resolution of 15 µm. Finally, using optical-resolution photoacoustic microscopy (OR-PAM), we show intra-cellular localization of lacZ expression, with a lateral resolution of a fraction of a micron. These results suggest that PAT is a complementary tool to conventional optical fluorescence imaging of reporter genes for linking biological studies from the microscopic to the macroscopic scales.